Oxidation of Cyclopentanone by N-Chlorosuccinimide in Presence of Rhodium(III) Chloride as Catalyst in Acidic Medium - Srivastava, M.K.; Kumar, Dilip (Asian Journal of Chemistry, 2010)
Kinetic studies on oxidation of cyclopentanone by N-chlorosuccinimide reagent in presnece of rhodium(III) chloride as catalyst in acidic medium have been studied to obtain the order of reaction with respect to N-chlorosuccinimide.